Condition and productivity of oak stands in Ukrainian Steppe - Tkach, V. P.; Kobets, O. V.; Rumiantsev, M. H. (Forestry and Forest Melioration, 2019)
Introduction The research is relevant as it is necessary to evaluate a current state and mensuration features of the oak stands in Steppe and to compare specific aspects of growth and development of oak forests of different origins. Condition and productivity of oak stands have recently deteriorated due to climate change on the planet, a negative impact of abiotic, biotic and anthropogenic factors, and an excessively man-made load in some parts of Steppe. All that brought about weakening processes, dieback and decay of oak stands. The aim of the study was to analyze and assess a current condition and forest mensuration features of the Steppe oak stands of different origin, as well as to compare specific aspects of their growth and development. Materials and Methods We used the Ukrderzhlisproekt Production Association database of the forest fund of the enterprises subordinated to the State Forest Resources Agency of Ukraine to analyze the forest mensuration parameters of the stands. To do the research, we applied the methods of comparative analysis and mathematical statistics according to standard mensuration approaches and the complex forest subdivision into districts in Ukraine. Results The Steppe oak stands are mainly concentrated in the northern part of Left-Bank Ukraine. More than half of the oak stands grow within the two administrative regions of Ukraine, namely Luhansk (38 %) and Donetsk (20 %) ones. 17.5 % of the Steppe oak forests grow within Kharkiv Region, 9 % in Dnipropetrovsk Region and 7 % in Odesa Region. By origin, coppice and planted stands dominate. Their area makes 51 % and 45 %, respectively. Middle-aged stands make 56 % of all oak stands in Steppe and 81 % of planted oak stands. The fact that young stands only make 7 % is a great concern. Oak stands with relative density of stocking 0.7 (44 %) and 0.8 (23 %) of the 3rd and 2nd productivity class prevail in the region. Their proportions are 42 % and 24 % of the whole area, respectively. Stands with relative density of stocking of 0.7 (51 %) dominate in coppice oak forests and those with relative density of stocking of 0.8 and more make only 16 %. Most of the Steppe oak stands grow in sites with high soil fertility but limited humidity – in dry (48 %) and fresh (38 %) fertile sites. In terms of functions they perform, protective and recreational forests prevail. There are no exploitation forests. Mostly simple, single-storey stands are growing in the study area. As for the composition, mixed oak stands prevail here. However, pure stands are also common. Mensuration parameters of the oak stands in the southern part of Steppe are lower than those in the northern part. According to the analysis of the oak stands’ parameters, no significant differences were found in forest management in stands of different origin and growing in different forest site types. There is an urgent need to take measures aimed at optimizing the age structure and productivity of oak stands in the region. Conclusions The oak stands in Steppe mainly grow in dry and fresh fertile sites with high trophic conditions but limited humidity, which affects their productivity. The stands in the Left-Bank part of the northern Steppe have higher productivity, regardless of their origin. The oak stands in the region perform important ecological functions. Most of them are protective and recreational forests. However, their division by functions requires additional verification. Age structure of the oak stands in Steppe is unbalanced. Mature and overmature coppice stands are getting formed over large areas, and their condition is steadily deteriorating. As a result, it’s getting more and more difficult to the oak stands to perform their functions. In order to improve the condition and optimize the structure of the stands, as well as to increase their productivity, it is necessary to implement area-based and typologically-based forestry practices, which take into account the origin and functional purpose of oak stands. Moreover, it is necessary to reconsider the oak stands’ maturity ages. 4 Figs., 4 Tables, 13 Refs.